Aeronautical publications and flight permits processing system - Mukwembi, Aluis (Midlands State University, 2017)
Aeronautical Publications and Flight Permits Processing System is a web-based computer system that automates all the processes that are involved in issuing flight permits, as well as recording and management of publications. Its major thrust is to provide a secure platform to issue flight permits for over flight and landing, and to conduct Airport surveillances online. The system deals with the creation and management of applicants or operators’ accounts since some Aircraft operators have prepaid accounts managed by the AIS permits office. Usually at the end of every month statements are sent to the prepaid account holders as a breakdown of permits issued that month and the remaining balance. The system was developed to address the weaknesses of the old system. MYSQL, WampServer, php and java scripts are the tools that were used in the development of the new system.